2011
DOI: 10.1021/nn2035044
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Multipolar Longitudinal and Transversal Surface Plasmon Modes in Nanowire Dimers

Abstract: We study the transversal and longitudinal localized surface plasmon resonances in single nanowires and nanowire dimers excited by the fast traveling electron beam in a transmission electron microscope equipped with high-resolution electron energy-loss spectroscopy. Bright and dark longitudinal modes up to the fifth order are resolved on individual metallic nanowires. On nanowire dimers, mode splitting into bonding and antibonding is measured up to the third order for several dimers with various aspect ratio an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 47 publications
11
93
2
Order By: Relevance
“…Longitudinal plasmon redshifts and transverse plasmon blueshifts and the apparition of higher longitudinal plasmon modes when the nanoparticle sizes and aspect ratios increase have already been predicted [126] and experimentally demonstrated in the literature [46][47][48]. Figures 7 and 8 demonstrate that the longitudinal resonance frequencies of the Au nanoparticles in a silica matrix are tunable to a high degree by adjusting their lengths and diameters.…”
Section: Experimental and Analytical Plasmonic Dispersion Relationsupporting
confidence: 63%
“…Longitudinal plasmon redshifts and transverse plasmon blueshifts and the apparition of higher longitudinal plasmon modes when the nanoparticle sizes and aspect ratios increase have already been predicted [126] and experimentally demonstrated in the literature [46][47][48]. Figures 7 and 8 demonstrate that the longitudinal resonance frequencies of the Au nanoparticles in a silica matrix are tunable to a high degree by adjusting their lengths and diameters.…”
Section: Experimental and Analytical Plasmonic Dispersion Relationsupporting
confidence: 63%
“…It was also demonstrated that energy-filtered transmission electron microscopy (EFTEM) can be equivalently employed to obtain the same information [8]. Plasmons in nanoparticles of other geometries were also visualized with SI methods [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In particular, to investigate SERS activity, Guiton et al employed STEM-EELS to probe the fields of plasmons in silver nanorods and correlated this with far-field scattering spectroscopy [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a number of different dimer geometries, such as sphere dimer [17], triangular dimer [18], nanoshell dimer [19], and nanowire dimer [20], were carried out experimentally and theoretically. However, the performance of a nanoparticle dimer with gain material is still inexplicit to our knowledge.…”
Section: Introductionmentioning
confidence: 99%